2015
DOI: 10.1016/j.juro.2015.05.105
|View full text |Cite
|
Sign up to set email alerts
|

Painful Bladder Filling and Painful Urgency are Distinct Characteristics in Men and Women with Urological Chronic Pelvic Pain Syndromes: A MAPP Research Network Study

Abstract: Purpose To describe bladder-associated symptoms in patients with urologic chronic pelvic pain syndromes (UCPPS) and to correlate these symptoms with urologic, non-urologic, psychosocial, and quality of life measures. Methods Participants were 233 women and 191 men with interstitial cystitis/bladder pain syndrome or chronic prostatitis/chronic pelvic pain syndrome in a multi-center study. They completed a battery of measures, including items asking if their pain worsened with bladder filling (“painful filling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 27 publications
3
64
0
2
Order By: Relevance
“…Other MAPP analyses examining cross-sectional clinical and neuroimaging data have also found more similarity than differences across men and women with UCPPS 5, 2930 . Also, neither income level (as a marker of social economic status) nor UCPPS chronicity were significant predictors of outcome.…”
Section: Discussionmentioning
confidence: 95%
“…Other MAPP analyses examining cross-sectional clinical and neuroimaging data have also found more similarity than differences across men and women with UCPPS 5, 2930 . Also, neither income level (as a marker of social economic status) nor UCPPS chronicity were significant predictors of outcome.…”
Section: Discussionmentioning
confidence: 95%
“…By definition, all women in the MAPP cohort were diagnosed with IC/BPS, while men may have either IC/BPS or CP/CPPS. Therefore, the female MAPP participants were found to exhibit more ‘bladder-centric’ symptoms than the male participants 16 . This could potentially have an impact on HCS, as bladder-centric symptoms could increase the likelihood of certain treatments/procedures to manage pain (e.g., cystoscopy, bladder instillations).…”
Section: Discussionmentioning
confidence: 93%
“…Painful filling is described as pain that worsens with the degree of bladder filling. The pain may be relieved at least partially by urination [26][27][28]. Painful urgency is described as the urge to urinate due mainly to pain, pressure, or discomfort, but not to fear of incontinence [26].…”
Section: Bladder-specific Features and Diagnosis Of Bps/icmentioning
confidence: 99%
“…The organ specific-bladder domain was positive in 33% of their patients. A research network study showed that 75% of all men with BPS/IC or CP/CPPS had painful filling or painful urgency [26].…”
Section: Prudent Approach To Chronic Pelvic Pain In Malesmentioning
confidence: 99%